Mediating effect of eating pattern on the relationship between television exposure and caries in children - Ayah Qassem SHQAIR; Matheus dos Santos FERNANDEZ; Francine dos Santos COSTA; Karen JANSEN; Janaína Vieira dos Santos MOTTA; Ricardo Azevedo da SILVA; Vanessa Polina da COSTA; Marília Leão GOETTEMS (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Behavioral characteristics may also take part in the etiology of dental caries. Sedentary behavior, especially watching television, is associated with increased intake of foods high in fat or free sugar, which could influence the occurrence of dental caries. The aim of this study was to assess the mediating effect of eating pattern on the relationship between television exposure time and the presence of dental caries in children. A cross-sectional study was conducted with a representative sample of 580 parent-child dyads with children aged 7 to 8 years in 20 public schools in Pelotas, Brazil. Parents or legal guardians were interviewed and provided information on demographic/socioeconomic data, children's daily television exposure time, and answered the Biological Rhythms Interview for Assessment in Neuropsychiatry for Kids (BRIAN-K-eating pattern domain). Caries was evaluated through clinical examination. The mediating effect of eating pattern on the relationship between television exposure and presence of dental caries was estimated using the parametric g-formula. Prevalence of dental caries was 63%, and 22% of children watched TV 4 or more hours per day. Television exposure had no direct effect on the dental caries experience [odds ratio (OR): 1.05 (95% confidence interval (95%CI): 0.92-1.19)]. Nevertheless, difficulty maintaining regular eating pattern mediated the natural indirect effect of television exposure time (≥ 4 hours/day) on dental caries experience [OR: 1.07 (95%CI): 1.01-1.14)]. The results of this study confirm the indirect pathway between television viewing and dental caries and the role of disordered eating patterns in this association.